Urban Unemployment in Nepal with Reference to Engineering Graduates of Kathmandu - Shakya, Punneshori (Journal of the Institute of Engineering, 2011)
The greater percentage of the graduates living in and outside Nepal is employed but they are not satisfied with the employment due to less salary scale. The respondents were from 23-50 age groups who graduated in between 1989 to 2000. Eighty one percentages of the respondents are currently living in Kathmandu valley, fourteen percentages are outside the valley in Nepal and five percentages are currently outside Nepal. The origin of the graduates is almost equally from both Kathmandu valley and outside the valley. The graduates are from various engineering backgrounds such as mainly from civil engineering followed by electrical and electronics engineering, architecture engineering, computer engineering and mechanical engineering. The survey shows that seventy seven percentages are not satisfied with their salary as the income range is not sufficient. This underemployment has led to economic, social and psychological problems. The survey reveals that political instability in the country is the main cause for current unemployment or underemployment followed by lack of opportunities and corruption. The respondents expressed that with political stability in the country organizational development can be enhanced which plays significant role in the employment process. Better education with proper educational policies also leads to skilled graduates that can meet the demand of the global market. According to the survey government is mainly responsible for the unemployment problem in the country and government should play an important role in formulating better economic policies, political stability with secured opportunities for investors and organizational development through international links for better employment opportunities establishing new job areas. Key words: Urban Unemployment; Engineering Graduates DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5126 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 301-310 Uploaded Date: 20 July, 2011